Manajemen Tata Kelola Stok Barang dan Display Produk untuk Meningkatkan Visual Merchandising - Nurhayati Nurhayati; Anas Khair Prikurnia; Addini Aliran Anwari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This report presents the results of a fieldwork internship focused on optimizing operations at By. Diara. The primary issue underlying this activity is the importance of balancing stock availability in the warehouse with the effectiveness of displays in the sales area to attract consumer interest. The objective of this internship is to implement a systematic stock management system and design a product display strategy that aligns with visual merchandising principles. Data collection methods included participant observation, interviews with field supervisors, and hands-in practice in inventory management and display arrangement. Stock management was conducted through product categorization based on Stock Keeping Units (SKU) and regular monitoring of incoming and outgoing goods. Visual merchandising enhancements were implemented through mannequin arrangement, lighting, and product color grouping to create a comfortable shopping flow. The results of this activity demonstrated that efficient inventory management can expedite the process of fulfilling customer needs and reduce the risk of stockpiling outdated merchandise. Furthermore, thematically updating product displays has been shown to enhance the boutique's visual appeal and make it easier for customers to find the products they desire. Overall, the integration of efficient inventory management and attractive visual merchandising is a key factor in enhancing By.Diara's professional image and sales performance.